Development of a Coordination System Design Based on Problem-Based Learning to Improve the Critical Thinking Ability of Grade XI Students - Axioma Salsabila Aniq; Endah Peniati (Journal of Biology Education, 2024)
The critical thinking skills of students in class XI SMAN 1 Bawang are low because of their lack of active participation. Students rely too much on the teacher, so they have difficulty mastering the coordination system material. This study aims to describe the characteristics of the diktat, analyze its feasibility, and analyze the improvement of students' critical thinking skills after using the problem-based learning and coordination system diktat. This research is a type of development research (Research and Development) with the ADDIE model. The subjects of this study were students of classes XI and XII MIPA SMAN 1 Bawang in the even semester of the 2022–2023 academic year. The sampling used the purposive sampling technique. The readability of the problem-based learning-based coordination system dictated by 18 XII grade students in the small-scale test obtained a result of 81.69% with a very feasible category.  The results of this study indicate that the problem-based learning-based coordination system dictates self-directed, self-contained, adaptive, user-friendly, and attractive appearance characteristics. The results of lecturer validation of the feasibility of the diktat of 95.83%, teacher assessment of 86.67%, and student responses of 77.36% showed an average of 86.62% that the developed product was very feasible to use in learning the coordination system. Furthermore, the effectiveness of the problem-based learning-based coordination system diktat was tested by involving 107 students from three XI MIPA classes. 92.53% of students got a complete score of KKM (70). There were differences in students' critical thinking skills after the pretest and post-test. The average n-gain score obtained in the student critical thinking ability test was 0.63 with moderate criteria. The conclusion of this research is that the problem-based learning-based coordination system dictate meets the characteristics of a dictate, is very feasible to use in learning, and is effective because it can improve the critical thinking skills of grade XI students of SMAN 1 Bawang on coordination system material.